A competência tributária para instituição do adicional do imposto sobre a circulação de mercadorias e sobre prestações de serviços para o fundo de combate e erradicação da pobreza: da ideologia à função. - Melo Junior, João Alves de (2019)
This research takes an approach on the tax jurisdiction to institute the additional Tax on the Circulation of Goods and Services Provision (ICMS) on products and services superfluous to the Fund for Combating and Eradicating Poverty, with the objective of analyzing the observance of the meaning minimum of the superfluous word in the structuring of the Matrix Tax Incidence Rule. The theoretical lines of Logical-Semantic Constructivism were considered for analysis. The hypothesis presented is of failures in the process of positivation and normative derivation for unconstitutional enlargement of the tax jurisdiction in times of fiscal austerity. For that, the analytic-deductive method was used in order to establish the premises for further conclusions. The itinerary of the research begins with the demonstration of tax jurisdiction as a rationality of tax selfconsent in deliberative democracy, penetrating the philosophical bases of constructivism, and then reaching the ideology, structure and function of the constitutional authorization to institute said additional. Finally, to test the hypothesis, the materialities provided for in the legislations of the 23 (twenty-three) tax entities that already exercised the competence under study were analyzed. The results point to a distortion of the semantic limits of the concept of superfluous (like the taxation of mineral water).